2011
DOI: 10.1186/1471-213x-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated gene expression during gilthead sea bream skeletogenesis and its disruption by nutritional hypervitaminosis A

Abstract: BackgroundVitamin A (VA) has a key role in vertebrate morphogenesis, determining body patterning and growth through the control of cell proliferation and differentiation processes. VA regulates primary molecular pathways of those processes by the binding of its active metabolite (retinoic acid) to two types of specific nuclear receptors: retinoic acid receptors (RARs) and retinoid X receptors (RXRs), which promote transcription of downstream target genes. This process is well known in most of higher vertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 95 publications
4
28
0
Order By: Relevance
“…The rise in col1a1 expression at 35 dph was consistent with earlier results in the gilthead sea bream, in which col1a1 expression was low up to 29 dph and was significantly upregulated between 29-37 dph (Fernández et al 2011). A similar expression pattern was also observed during European sea bass development whereby col1a1 expression was positively correlated with bone development (Darias et al 2008) suggesting that col1a1 is of huge biological importance by providing mechanical support in both the growing skeleton and the increasing muscle fiber organization.…”
Section: Gene Expression and Muscle Developmentsupporting
confidence: 88%
“…The rise in col1a1 expression at 35 dph was consistent with earlier results in the gilthead sea bream, in which col1a1 expression was low up to 29 dph and was significantly upregulated between 29-37 dph (Fernández et al 2011). A similar expression pattern was also observed during European sea bass development whereby col1a1 expression was positively correlated with bone development (Darias et al 2008) suggesting that col1a1 is of huge biological importance by providing mechanical support in both the growing skeleton and the increasing muscle fiber organization.…”
Section: Gene Expression and Muscle Developmentsupporting
confidence: 88%
“…(2001), their gene expression results support our findings of OC protein accumulation in the notochord. Moreover, the increased OC and MGP protein accumulation in gilthead sea bream juveniles fed with hypervitaminosis A was in agreement with its higher gene expression in gilthead sea bream larvae fed with high dietary VA doses (Fernández et al., 2011). These results correlated with previous studies showing increased co‐transcription of both chondrogenic and osteogenic markers in the notochord of Atlantic salmon during the pathogenesis of spinal fusions (Ytteborg et al., 2010a,b).…”
Section: Discussionsupporting
confidence: 53%
“…Hypervitaminosis A is likely to ultimately cause specific gene expression disruption at critical development stages [48]. A recent report has indicated that a high dietary intake of retinol can lead to bone marrow hypoxia and diaphyseal endosteal mineralization in rats [49].…”
Section: Discussionmentioning
confidence: 99%